The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1348/026151002760390800
|View full text |Cite
|
Sign up to set email alerts
|

Newborns' local processing in schematic facelike configurations

Abstract: The goal of the study was to provide a direct comparison of newborns' ability to process and store, over a 2min delay, the shape of the internal local elements of schematic facelike and non-facelike patterns. Two experiments were carried out using a visual habituation technique with an infant control procedure. The results demonstrate that newborns discriminated between two schematic facelike and nonfacelike configurations that differed exclusively for the shape of the internal local elements (Expt 1), and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…A conflict between different facial regions of interest might be in play. It is now established that neonates are able to discriminate the inner features of a face (Simion, Farroni, Cassia, Turati & Barba, 2002; Turati & Simion, 2002), and prefer photographs of real faces with eyes open rather than closed (Batki, Baron‐Cohen, Wheelwright, Connellan & Ahluwalia, 2000), or faces with direct rather than averted gaze (Farroni, Csibra, Simon & Johnson, 2002). Newborn infants should thus attribute more interest to a face than to an isolated mouth.…”
Section: Discussionmentioning
confidence: 99%
“…A conflict between different facial regions of interest might be in play. It is now established that neonates are able to discriminate the inner features of a face (Simion, Farroni, Cassia, Turati & Barba, 2002; Turati & Simion, 2002), and prefer photographs of real faces with eyes open rather than closed (Batki, Baron‐Cohen, Wheelwright, Connellan & Ahluwalia, 2000), or faces with direct rather than averted gaze (Farroni, Csibra, Simon & Johnson, 2002). Newborn infants should thus attribute more interest to a face than to an isolated mouth.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the existing literature on human infants leaves unresolved the question of whether there is a specific or non‐specific mechanism, which could explain the spontaneous preference for face‐like stimuli seen in newborns. Part of the controversy may depend upon the effect of early learning (for evidence on fast learning about the appearance of faces shortly after birth, see Bushnel, Sai & Mullin, 1989; Simion, Farroni, Macchi Cassia, Turati & Dalla Barba, 2002; Turati, Macchi Cassia, Simion & Leo, 2006; Walton & Bower, 1993). Carefully controlled studies with animals could help resolve this issue, but surprisingly little research has been aimed at investigating what specific features of the head region stimulate CONSPEC in chicks.…”
Section: Introductionmentioning
confidence: 99%
“…Past research has shown that human neonates already prefer normally configured facial features and are more likely to track a face‐like pattern than a non‐face‐like pattern (Goren, Sarty, & Wu, ). Further experiments have shown that newborns not only prefer faces but also more generally top‐heavy patterns (Valenza, Simion, Cassia, & Umilta, ) and specifically, top‐heavy patterns with a curvilinear external contour (Simion, Farroni, Cassia, Turati, & Dalla Barba, ). This initial attentional preference towards faces is thought to produce biassed input, resulting in processing advantages for the most commonly encountered types of faces.…”
mentioning
confidence: 99%